Experimental investigation of multiple oscillating water column wave energy converters integrated in a floating breakwater: Wave attenuation and motion characteristics. (June 2020) - Howe, Damon; Nader, Jean-Roch; Macfarlane, Gregor
Abstract: This article is Part B of a study into the proof-of-concept of a floating breakwater integrated with multiple Oscillating Water Column (OWC) Wave Energy Converters (WEC). The structure is designed for nearshore and offshore applications and the investigation was performed through model scale hydrodynamic experimentation. Part A introduced the concept and the experiments performed, followed by an investigation into the energy extraction performance of the installed OWC devices [1]. This paper covers the impact of the OWC WECs on the floating breakwater's wave attenuation and motion characteristics. As this investigation took a proof-of-concept approach, a soft mooring system was configured to the device in order to establish the general behaviour of the structure. Results indicate that the pitch motion was the most detrimental motion in terms of OWC device performance, but this is expected to be mitigated with incorporation of realistic mooring arrangements. Additionally, findings infer that in majority of cases, OWC device integration has beneficial impacts on both the wave attenuation and motions of the breakwater structure, lending further credence to the economic and performance viability of the concept.